2019
DOI: 10.6026/97320630015333
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of pyridoxineto flaxseed cake in poultry feed improves productivity of omega-3 enriched eggs

Abstract: Flaxseed cake produced during flax oil production is rich in protein, and could be utilized in the production of omega-3 enriched eggs or value added eggs. But the presence of anti-nutrients in flaxseed cake adversely affects the bird and egg characteristics. Supplementation of pyridoxine may prove beneficial as noted by earlier research. In our study, we divided 30 layer birds into three groups and supplemented them with different combination feeds containing: (A) control ration, (B) fresh flax seed cake with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…The results obtained in the present study showed that by using vegetable sources (flaxseed meal, rapeseed meal and rice bran) in laying hens' diet, the yolk cholesterol concentration can be decreased. Similar results were obtained by Khan (2019) when using a combination of flax seeds (2%), flax cake (5%) and vitamin B6 (40 mg / kg diet) in laying hens' diets, obtaining a positive effect on the lowering egg cholesterol. In another similar study, Faitarone et al (2013) evaluated the effects of supplementation with different vegetable oils on egg cholesterol levels and their nutritional composition.…”
Section: Egg Cholesterol Contentsupporting
confidence: 79%
“…The results obtained in the present study showed that by using vegetable sources (flaxseed meal, rapeseed meal and rice bran) in laying hens' diet, the yolk cholesterol concentration can be decreased. Similar results were obtained by Khan (2019) when using a combination of flax seeds (2%), flax cake (5%) and vitamin B6 (40 mg / kg diet) in laying hens' diets, obtaining a positive effect on the lowering egg cholesterol. In another similar study, Faitarone et al (2013) evaluated the effects of supplementation with different vegetable oils on egg cholesterol levels and their nutritional composition.…”
Section: Egg Cholesterol Contentsupporting
confidence: 79%
“…Vlaicu and Panaite [60] demonstrated the effectiveness of pumpkin seed sterols in reducing egg yolk cholesterol. In agreement with the conclusions of our study, the data available in the specialized literature show that supplementing the diets of laying hens with flax seeds [61,62], hemp seeds [11], and rapeseed [63] led to a decrease in cholesterol concentration in yolks. However, other studies reported that the fat source in the diets of hens does not influence the level of cholesterol in egg yolks [64].…”
Section: Egg Yolk Cholesterol Contentsupporting
confidence: 93%
“…Polyunsaturated fatty acids (PUFAs) and α-linolenic acid (ALA), in particular, are abundant in most flaxseed species (Kajla et al 2014;Lan et al 2020;Chandran 2021). Flaxseeds are rich in ALA, an omega-3 fatty acid; flaxseed oil contains 45-52% ALA (Khan 2019). Almost every part of the flaxseed plant is helpful in some way for feeding livestock and poultry.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the seed strain and processing settings, the amount of residual oil in FC can be increased from approximately 1% to over 16%. This makes FC also a potential method for increasing the amount of omega-3 fatty acids in eggs, milk and meat (Khan 2019). Recently, there has been an extended mismatch in supply and demand for traditional resources of protein feeds, leading to rising feed costs and reduced livestock and poultry production sustainability.…”
Section: Introductionmentioning
confidence: 99%